Resting heart rate as a determinant of fatigue - reforming - analysis of the impact of strength and strength training on the cadres curves - Filarecka, Agnieszka; Biernacki, Maciej (Journal of Education, Health and Sport, 2018)
Objectives. The overload occurring during the formation of motor features may be caused by insufficient regeneration of the fissures. Too intensive training can lead to reduced efficiency, but efficiency is developing on the borderline of possibilities. so you should find the moment when the player presents the first symptoms of fatigueThe aim of data analysis is to show the relationship of the pulse curve as a sign of training fatigue and the impact of changes in altitude on the adaptation of the cardiovascular system.Material and methods. The data from the training camp of Polish senior canoeists during the climat training camp in Belmeken in Bulgaria were used for the study. Resting heart rate were investigated on solids between 6:00 am and 8:00 pm behind an assumed heart rate on the chest. Morning results were compared with the evening of the previous day.Results.Morning and evening heart rate are indicative of fatigue,The heart rate changes with altitude.The regeneration level can be read from the intersection of the pulse line. Strength training is a more stressful training. The level of regeneration after endurance training is greater compared to strength training. 24-hour training break has a beneficial effect on regeneration, prolonged physical efforts require longer regeneration timeConclusions. Morning and evening heart rate is a good indicator of fatigue. Monitoring of the parameter allows to avoid overtraining before other signs of fatigue can be felt. During the development of strength and endurance monitoring of the heart rate will help choose the right training and determine rest and recovery periods.